Wczesnoszkolna edukacja „z duszą” w Szkole Podstawowej nr 83 „Łejery”w Poznaniu - Sadowska, Katarzyna (Studia Edukacyjne, 2025)
The study aims to show the beginnings of the essence and specificity of early school education implemented in the Emilia Waśniowska Primary School No. 83 in Poznań, where children learn through art, democratic education and a child-centered education. The research problem is contained in the question: How did early school education come into being and what are its characteristics at Primary School No. 83 in Poznań? The author analyses (existing and elicited) sources such as studies, magazine articles, archival films posted on websites related to “Łejery”, press releases and information from the school website, documents received from “Łejery” teachers in electronic form, “Łejery” own publications and occasional publications related to the school. The elicited sources include the author’s interviews conducted in the school year 2024/2025 with Elżbieta Drygas and Jerzy Hamerski. The analysis concerns primarily the content of the sources. The study focuses on presenting the history of the creation of the “theatre school” and characterizing the concept of child education as particularly valuable in the context of Polish educational practice. The author’s analysis leads to the conclusion that the education of a child in Primary School No. 83 fosters the development of autonomy and creativity, supports the student’s resources in the area of knowledge and school skills, and enables effective social and emotional functioning.